155 Qualitative evaluation of a patient navigator program for children with developmental and mental health diagnoses - Yaseen, Wid (Paediatr Child Health, 2019)
BACKGROUND: Children with mental health and developmental diagnoses require social and community programs for therapy and support, yet few have adequate access to these services. To connect these families with necessary services and funding, a pediatric patient navigator program was launched for children with mental health and developmental diagnoses living in a large urban setting in Canada. The experiences, benefits, and limitations of a navigation program in this patient population have not been well documented. OBJECTIVES: To explore the experiences of various stakeholders with a new pediatric patient navigation program at an urban, inner-city pediatric clinic in Canada, as well as barriers and facilitators to successful program outcomes. DESIGN/METHODS: This was a qualitative study using a formative research framework. In-depth interviews (IDIs) and participant observations were conducted with patients’ caregivers, general and developmental pediatricians, allied health staff, clinic administrators, and the patient navigator. Data were recorded, transcribed, and coded using deductive and inductive coding methods by two independent coders. Coded excerpts were analyzed within and across stakeholder groups using thematic analysis and supported by group discussion. RESULTS: A total of 25 IDIs and 3 participant observations were conducted across all stakeholder groups. High inter-rater reliability was confirmed by pooled Cohen’s kappa coefficient of 0.85. Before the navigator, caregivers reported difficulty finding and receiving services while healthcare providers described their abilities to find services as ineffective. The navigator’s role was described as multifaceted: completing paperwork, finding funding options, offering emotional support, liaising between physicians and patients, and advocating with schools and agencies. Physicians emphasized the navigator’s support in reducing burnout and allowing for more focused medical visits, while caregivers felt personally supported and better able to access services. However, despite multiple workshops, healthcare providers’ understanding of referral criteria varied, which may lead to inappropriate referrals and longer wait times. CONCLUSION: Families and caregivers alike face challenges in accessing developmental and mental health services. Patient navigation programs may be a useful strategy to improve patient access to services in a supportive way. More research is needed to reveal the long-term impact of navigation programs on children’s developmental and health outcomes.